2017
DOI: 10.1088/1361-6501/28/3/034010
|View full text |Cite
|
Sign up to set email alerts
|

Comparing AFM cantilever stiffness measured using the thermal vibration and the improved thermal vibration methods with that of an SI traceable method based on MEMS

Abstract: PTB has developed a new contact based method for the traceable calibration of the normal stiffness of AFM cantilevers in the range from 0.03 N m−1 to 300 N m−1 to the SI units based on micro-electro-mechanical system (MEMS) actuators. This method is evaluated by comparing the measured cantilever stiffness with that measured by PTB’s new primary nanonewton force facility and by PTB’s microforce measuring device. The MEMS system was used to calibrate the stiffness of cantilevers in two case studies. One set of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The tiny differences observed in between cells and between single-cell and single-molecule experiments are likely due to variability of cells and random orientation of the Fg on the AFM tip. But, we cannot exclude that (i) the uncertainty on the calibration of the cantilever spring constant, and (ii) AFM datasets obtained with different cantilevers (thus of different spring constants, see Supplementary Tables 1 and 2 ) 28 also play a role in such small variability. We believe this strong interaction force originates from a DLL binding mechanism because: (i) biochemical analyses demonstrated that SpsD binds Fg through such mechanism, (ii) the high force, much stronger than that of typical protein–receptor interaction (from one to few hundreds of pN), is in the range of values recently reported for adhesins engaged in a DLL interaction 18 , 19 .…”
Section: Resultsmentioning
confidence: 99%
“…The tiny differences observed in between cells and between single-cell and single-molecule experiments are likely due to variability of cells and random orientation of the Fg on the AFM tip. But, we cannot exclude that (i) the uncertainty on the calibration of the cantilever spring constant, and (ii) AFM datasets obtained with different cantilevers (thus of different spring constants, see Supplementary Tables 1 and 2 ) 28 also play a role in such small variability. We believe this strong interaction force originates from a DLL binding mechanism because: (i) biochemical analyses demonstrated that SpsD binds Fg through such mechanism, (ii) the high force, much stronger than that of typical protein–receptor interaction (from one to few hundreds of pN), is in the range of values recently reported for adhesins engaged in a DLL interaction 18 , 19 .…”
Section: Resultsmentioning
confidence: 99%
“…As calibration errors of up to 15% come with cantilever-based force measurements, 29 the precision and therefore the comparability of individual SMFS experiments is limited by the accuracy of the calibration of the cantilever spring constant. This limitation can be circumvented by presenting a set of molecules in a covalently linked microarray format on a single glass slide in predetermined positions.…”
Section: Resultsmentioning
confidence: 99%
“…By using a single cantilever through all conditions, calibration errors of up to ~15% that normally result from individual AFM-based SMFS measurements can be circumvented 20 . We therefore obtain comparable absolute force data of all probed cohesins both with and without the dockerin bound.…”
Section: Resultsmentioning
confidence: 99%